Intercultural Sensitivity of Public School Principals in Brazil (Desenvolvimento em Questão, 2022)
The aim of this study is to measure the level of intercultural sensitivity of public school principals in Brazil, and to seek evidence about which individual, institutional, socioeconomic, and localization characteristics are related to this aspect. Intercultural sensitivity translates behavioral aspects into situations of interaction between individuals from different cultures. It is one of the important competencies for education professionals to better perform their pedagogical work within the school environment. In order to achieve the aim of this work, an Intercultural Sensitivity Index (ISI) was proposed, and then, econometric regressions were made in OLS to correlate these characteristics with the proposed index. From the results of these models, it was proposed a profile of public school principals in relation to intercultural sensitivity.  With the evidence obtained by the model, orientation of public policies focused on the theme was proposed.